2023
DOI: 10.1093/mnras/stad343
|View full text |Cite
|
Sign up to set email alerts
|

The TIME Table: rotation and ages of cool exoplanet host stars

Abstract: Age is a stellar parameter that is both fundamental and difficult to determine. Among middle-aged M dwarfs, the most prolific hosts of close-in and detectable exoplanets, gyrochronology is the most promising method to assign ages, but requires calibration by rotation-temperature sequences (gyrochrones) in clusters of known ages. We curated a catalog of 249 late K- and M-type (Teff=3200-4200K) exoplanet host stars with established rotation periods, and applied empirical, temperature-dependent rotation-age relat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 181 publications
1
11
0
Order By: Relevance
“…We therefore conclude that GJ 367 is a rather slowly rotating, old star with a low magnetic activity level, rather than a young M dwarf. This conclusion is consistent with a recent study by Gaidos et al (2023), who measured an age of 7.95 ± 1.31 Gyr from the M-dwarf rotation-age relation.…”
Section: The Low Level Of Magnetic Activity Inferred By Thesupporting
confidence: 93%
“…We therefore conclude that GJ 367 is a rather slowly rotating, old star with a low magnetic activity level, rather than a young M dwarf. This conclusion is consistent with a recent study by Gaidos et al (2023), who measured an age of 7.95 ± 1.31 Gyr from the M-dwarf rotation-age relation.…”
Section: The Low Level Of Magnetic Activity Inferred By Thesupporting
confidence: 93%
“…Clusters such as NGC 6791 (8 Gyr; Chaboyer et al 1999), or else a precise set of asteroseismic calibrators (e.g., van Saders et al 2016) might be the most plausible paths toward the goal of going older, though the complicating effects of stellar evolution for F and G dwarfs bear consideration. For M dwarf gyrochronology (e.g., Gaidos et al 2023), the existence of a slow-sequence for M67 implies that the M-dwarfs do eventually converge to a slow sequence; future studies should aim to determine when exactly this occurs.…”
Section: Future Directionsmentioning
confidence: 99%
“…While stellar ages are notoriously poorly constrained (Adams et al 2005), the age distribution of planet host stars in the Solar neighborhood was shown to be broadly consistent with uniform (Reid et al 2007;Gaidos et al 2023). For our synthetic stars, we thus drew random ages from a uniform distribution from 0 to 10 Gyr.…”
Section: Stellar Luminosity Evolutionmentioning
confidence: 99%